'Love mounts to the throne with law': citizenship in Northern Ireland and Seamus Heaney's Antigone. Issue 2 (3rd July 2021) - Kenny, David
ABSTRACT: In this paper, I examine disputes about citizenship in Northern Ireland though the lens of poet Seamus Heaney's 2004 version of Antigone, The Burial at Thebes. Citizenship and identity in Northern Ireland – if people are Irish or British – has been a central issue of the conflict there. The 1998 peace agreement promised to allow people to identify however they wished, and not be forced to adopt an identity they rejected. But recent controversies, including Brexit and a major legal challenge, have shown that the legal concept of citizenship has not been able to fulfil this promise. Sophocles' Antigone presents a great clash between the authority of the State and deep personal/morality commitments, and the tragedy that result. Heaney's Antigone casts light on the fundamental clash at the centre of citizenship, and points us toward a flexible, contextual multi-level citizenship as a solution to law's rigid conception of what a citizen must be.